Galerkin approximation and the strong solution of the Navier-Stokes equation. (2000) - Breckner, Hannelore
Abstract : We consider a stochastic equation of Navier-Stokes type containing a noise part given by a stochastic integral with respect to a Wiener process. The purpose of this paper is to approximate the solution of this nonlinear equation by the Galerkin method. We prove the convergence in mean square.